Determinants of eating habits of UP Diliman students - Alivia, Giulia L. (School of Economics, University of the Philippines Diliman, 2018)
Different factors affect the eating habits of an individual. In a college setting, the pursuit of greater independence from parental supervision coupled with a likely perceived drastic change of environment are crucial for the development of dietary consumption choices. Using the data from a self-administered survey, this study investigates the different determinants of eating choices of 333 University of the Philippines Diliman undergraduate students. This paper_s empirical model is heavily based on Akbay, Tiryaki and Gul (2007), who identify consumer characteristics that influence the consumption of junk food products in Turkey using the proposed conceptual framework. The current model is estimated using ordered probit and probit models to obtain the corresponding marginal effects and probabilities. The results show that parental supervision, diet restrictions, allowance, alcohol consumption, smoking habits, physical activity, current housing type, and access to homemade meals are significant at the 90-95 percent confidence level in influencing the students choice of food options. The results indicate that diet restrictions, access to homemade meals, and high frequencies in physical activity positively affect students healthy eating habits, while alcohol consumption and smoking habits negatively affect the students healthy eating habits. The findings seeks to help students identify which factors affect their eating habits to increase their consciousness in the consumption of healthy options.